2016
DOI: 10.1155/2016/3059434
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Study in Learning Curves of Two Different Intracorporeal Knot Tying Techniques

Abstract: Objectives. In our study we are aiming to analyse the learning curves in our surgical trainees by using two standard methods of intracorporeal knot tying. Material and Method. Two randomized groups of trainees are trained with two different intracorporeal knot tying techniques (loop and winding) by single surgeon for eight sessions. In each session participants were allowed to make as many numbers of knots in thirty minutes. The duration for each set of knots and the number of knots for each session were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Finally, the non-dominant needle driver grasps the tail end of the suture and secures the first throw. The following throw is performed with a reverse wind and then a throw with a forward wind (Figure 2 ) [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Finally, the non-dominant needle driver grasps the tail end of the suture and secures the first throw. The following throw is performed with a reverse wind and then a throw with a forward wind (Figure 2 ) [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Vossen et al have reported in 29 trainee learning curves with one- or two-phase exponential decay model, the latter fitting their experimental points only marginally better [ 20 ]. Zhou et al [ 28 ] and Thiyagarajan et al [ 29 ] have also reported in 20 trainee learning curves with an exponential decay shape. Consistent with our results, the duration of the first knot varied with the previous laparoscopic experience being lower in more experienced trainees [ 20 ].…”
Section: Discussionmentioning
confidence: 98%
“…Vossen et al have reported in 29 trainees learning curves with mono- or bi-exponential decay, the latter fitting their experimental points only marginally better [ 25 ]. Zhou et al [ 28 ] and Thiyagarajan et al [ 29 ] have also reported in 20 trainees learning curves with an exponential decay shape.…”
Section: Discussionmentioning
confidence: 99%